Remarks at the Foreign Correspondents Club of Japan, Tokyo, March 13, 2015 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, discusses the two goals that shape the mission of the World Bank Group: ending extreme poverty by 2030 and boosting shared prosperity. He speaks the need to accelerate a kind of economic growth that’s more inclusive, socially sustainable, and protects the environment. He talks about climate change. The frequency, intensity, and duration of extreme climatic events will increase. Droughts, earthquakes, and typhoons will only become worse in the future. He appreciates Japan’s focus on doing things before a disaster strikes, as it saves lives and money. He talks about working to refocus developing countries on prevention and preparedness when it comes to disaster risk management. He commends Japan that has been supportive of the World Bank Group’s efforts to make innovative financing mechanisms available to governments of developing countries. He appreciates Japan's contribution towards Ebola crisis. He concludes by saying that the Japan's accumulated wisdom has shown the world that taking the proper precautions can save thousands of lives as well as billions of dollars in lost economic growth.